Phylogenetic Tree Analysis for Ongole Grade (Kebumen Cattle) Based on Partial SRY Gene - Hartatik, Tety; Hariyono, Dwi Nur Happy; Insani, Galuh Adi; Sumadi, Sumadi; Maharani, Dyah; Sidadolog, Jafendi Hasoloan Purba (2017)
Ongole grade (PO Kebumen cattle) has been registered and regarded as a valuable animal genetic resources in Indonesia. As an initial step in assesing the genetic relationship to other breeds, therefore phylogenetic analysis and calculation of genetic distances have been conducted using partial SRY gene. To perform a phylogenetic tree, a total of 14 Kebumen cattles were fistly aligned to 43 Madura cattle and 12 genbank references (Bubalus bubalis, Bos javanicus, Capra hircus, Bos taurus, and Bos indicus) of 928 bp SRY gene sequences using MEGA ver.7.0 software and the phylogenetic tree was performed using Neighbor-Joining and UPGMA (Unweighted Pair Group Method with Arithmetic Mean) methods. All of the alignment sequences of Kebumen cattle, were in monomorphic as well as in Madura 1 and Madura 2. The main results indicated that Kebumen cattle have a close relationship to both Bos indicus and Madura cattle (Madura 1 and Madura 2) with the closest genetic distance 0.000, indicating no different sequences. Hence, it can be implied that they shared a common ancestor. Moreover, the Kebumen cattle shared a distant relationship to both Bubalus bubalis (0.030) and Capra hircus (0.065). In our suggestion, these result will provide useful information for preservation and conservation strategies for Kebumen cattle as an Indonesian animal genetic resources.